Unleashing Entrepreneurial Potential: How Non-Economics Students Dive into the World of Business - Sya'diah, Sri Djatnika; Joeliaty, Joeliaty; Wijayabrana, Caturdria (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
In overcoming the complexity of the global world of work, non-economics students need to increase their interest and involvement in entrepreneurial activities to reduce the unemployment rate in Indonesia. This study aims to analyze the interest and participation of Non-Economics Students in entrepreneurship. This literature review uses secondary data, especially referring to articles related to the research focus. The research focuses on entrepreneurship among non-economic study program students. The research results show that non-economic students' interest in entrepreneurship is still low. Negative views, lack of knowledge, and minimal environmental support hamper their involvement in entrepreneurial activities. Factors influencing interest and involvement involve family environment, entrepreneurial education, self-confidence, and institutional support. Efforts are needed to increase non-economic students' interest in entrepreneurship. Improvements in curriculum approaches and educational environments are required to increase their involvement in entrepreneurial activities. Focusing on key factors can be the basis for improving educational policies and programs to encourage the participation of non-economic students in the world of entrepreneurship. This study highlights the critical gap in entrepreneurial interest and participation among non-economics students in Indonesia. Furthermore, the study offers valuable insights into the specific factors that influence non-economics students' involvement in entrepreneurship.